53rd AIAA Aerospace Sciences Meeting 2015
DOI: 10.2514/6.2015-0008
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Study of Flow Within Cavities with Complex Geometric Features

Abstract: This work examines simulation requirements for ensuring accurate predictions of compressible cavity flows. Lessons learned from this study will be used in the future to study the effects of complex geometric features, representative of those found on real weapons bays, on compressible flow past open cavities. A hybrid RANS/LES simulation method is applied to a rectangular cavity with length-to-depth ratio of 7, in order to first validate the model for this class of flows. Detailed studies of mesh resolution, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…The eddies (4) in the shear layer travel along the length of the cavity and impinge with the rear wall (5). The impinging of the shear layer on the rear wall which is known as the main acoustic source 11 generates vortex circulation zones (6) and acoustic waves which advance upwards (8). The vortex circulation zones advancing towards the anterior wall (7) interact with the shear layer and affect the separation period of the boundary layer from the surface.…”
Section: Mechanism Of Cavity Flowmentioning
confidence: 99%
See 2 more Smart Citations
“…The eddies (4) in the shear layer travel along the length of the cavity and impinge with the rear wall (5). The impinging of the shear layer on the rear wall which is known as the main acoustic source 11 generates vortex circulation zones (6) and acoustic waves which advance upwards (8). The vortex circulation zones advancing towards the anterior wall (7) interact with the shear layer and affect the separation period of the boundary layer from the surface.…”
Section: Mechanism Of Cavity Flowmentioning
confidence: 99%
“…The one-equation transport equation for the turbulent viscosity of Spalart-Allmaras, the other RANS model used for the DES model, is given in (6).…”
Section: Mathematical Modeling Of Turbulencementioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the aero-acoustic response of a weapons bay can strongly differ from the standard rectangular cavity. Typical weapons bay aerodynamic and acoustic response is strongly influenced by external factors, such as local design solutions, which alter the reference rectangular shape ( [5][6][7][8][9][10][11][12]). Dedicated studies have shown the strong influence of bay doors on the cavity.…”
Section: Introductionmentioning
confidence: 99%
“…Ön duvardan kavite içine doğru kopan Vorteks Yapıları (4) zaman bağlı karakterlerini korumalarının yanında, kopan bu yapıların Kavite Arka Duvarı ile Etkileşimi (5)kavite içinde Girdap Sirkülasyon Bölgelerini (6) oluşturmaktadır. Ön duvardan kopan vorteks ve girdap sirkülasyonun beslediği Zamana Bağlı Basınç Değişimi (7) Akustik Basınç Yayılımını (8) doğurmaktadır [3]. Akustik yayılım, arka duvardan ön duvara doğru takip ettiği yörüngesinde ön duvardan kopan vorteks yapılarını, akış alanındaki zamana bağlı değişimlere ek olarak etkilemekte ve vorteksin kopma sıklığını değiştirmektedir [1].…”
Section: Gi̇ri̇ş (Introduction)unclassified